Celtic inspirations - "Wilde, Lyn Webster" (London, 2004)
A Beautiful Collection Of Spiritual And Meditative Exercises, Providing A Fascinating Insight Into The Mystery And Beauty Of The Celtic Imagination. The Celts Were Not Only Great Warriors But Also A Deeply Creative And Mystical People. Today We Especially Appreciate Their Imaginative Myth-Making, Their Brilliant Design And Their Profound Sense Of Wonder And Magic - Three Elements That Combine In This Beautiful And Inspiring Gift Book. Celtic Inspirations Captures The Spirit Of The Druids And Bards In A Rich Collection Of Poetic Texts, Spiritual Insights And Meditative Exercises That Concentrate On The Universal Truths Of Celtic Wisdom - As Meaningful And Helpful Today As They Were In The Dark Ages. We Discover How To Heal Using Plants, How To Cast Spells, And How To Foretell The Future By Watching Birds In Flight; We Learn The Secrets Of King Arthur's Knights And The Truth About The Holy Grail. By Stepping Through The Door Of Celtic Wisdom With This Beautiful And Inspirational Book, We Are Given A Heartwarming And Enlightening Experience.
Keywords: Meditations